2018
DOI: 10.15421/2018_233
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of adverse environmental impacts caused by urban sewage: application of green soil fertilizers

Abstract: <p>This research was designed with the aim of feasibility study on the production of safe fertilizers from urban sewage sludge in Isfahan refinery and assessment of the nutritional value of produced fertilizers in comparison with standard. For this purpose, the effects of different ratios of sewage sludge and manure on different treatments (including: 0, 25, 40, 55, 70 and 85 % wt/wt) along with 15 % bulking materials (including dry residues of Pine trees and grass waste) were tested in a randomized comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example, Lukashe, et al [4] conducted an experiment where cow manure-waste paper fly ash mixture was inoculated with P. fluorescence, and concluded that the interaction between E. fetida and P. fluorescence could optimize the vermi-degradation of the mixture and increase the nutrient release and biological activity. Though organic nutrient sources like vermicomposts have been reported to be superior to inorganic nutrient sources in improving overall soil chemical, biological and physical properties, their adoption in conventional agriculture has been limited by their low macro-nutrient concentrations [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lukashe, et al [4] conducted an experiment where cow manure-waste paper fly ash mixture was inoculated with P. fluorescence, and concluded that the interaction between E. fetida and P. fluorescence could optimize the vermi-degradation of the mixture and increase the nutrient release and biological activity. Though organic nutrient sources like vermicomposts have been reported to be superior to inorganic nutrient sources in improving overall soil chemical, biological and physical properties, their adoption in conventional agriculture has been limited by their low macro-nutrient concentrations [2,8].…”
Section: Introductionmentioning
confidence: 99%